Refining soil organic carbon stock estimates for China’s palustrine wetlands - Kun Ma; Junguo Liu; Ying Zhang; Lauren E Parry; Joseph Holden; Philippe Ciais (Environmental Research Letters, 2015)
Palustrine wetlands (PWs) include all bogs, fens, swamps and marshes that are non-saline and which are not lakes or rivers. They therefore form a highly important group of wetlands which hold large carbon stocks. If these wetlands are not protected properly they could become a net carbon source in the future. Compilation of spatially explicit wetland databases, national inventory data and in situ measurement of soil organic carbon (SOC) could be useful to better quantify SOC and formulate long-term strategies for mitigating global climate change. In this study, a synergistic mapping approach was used to create a hybrid map for PWs for China and to estimate their SOC content. Total SOC storage in PWs was estimated to be 4.3 ± 1.4 Pg C, with a SOC density of 31.17 (±10.55) kg C m ^−2 in the upper 1 m of the soil layer. This carbon stock is concentrated in Northeast China (49%) and the Qinghai–Tibet Plateau (41%). Given the large pool of carbon stored in PWs compared to other soil types, we suggest that urgent monitoring programmes on SOC should be established in regions with very few datasets, but where PWs appear to be common such as the Tibet region and Northwest China.